CUSTOMER SATISFACTION ASSESSMENT THROUGH IMPORTANCE-PERFORMANCE ANALYSIS - Siska Ernawati Fatimah (International Journal of Innovative Technologies in Social Science, 2023)
The mini market business represents the modernization of traditional markets. However, with the enactment of Presidential Regulation No. 44/2016, which permits foreign retailers to open stores in Indonesia, foreign retailers have gained confidence in penetrating both major city malls and even trying their hand in smaller towns. The research aims to assess the quality of service and the trust associated with satisfaction using the Importance Performance Analysis (IPA) method. The population consists of all consumers in various mini markets in the city of Cirebon. The sampling technique utilized is random sampling. Data collection is done through questionnaires, and data analysis employs multiple regression analysis and the IPA method. The research results, based on multiple regression analysis, demonstrate a positive and significant influence between the variables of service quality and trust on customer satisfaction. Meanwhile, based on the IPA method, the average level of conformity reveals that satisfaction is at 90%. Therefore, it is apparent that 21 indicators are distributed across Quadrants A, B, C, and D, signifying a conformity in service quality and trust toward customer satisfaction.